De cómo aprovechar la crisis para que los pobres obtengan casa - Necochea, Andrés (Revista EURE - Revista de Estudios Urbano Regionales, 1988)
Through a literature review on housing policy in Latin America, the author explores the impact of the recent economic crisis on the housing sector of the Latin American countries. The article centers in the discussion of two hypothesis: Firstly, that the present scenario is favourable for housing policies focused on the needs of the very low income groups which traditionally have been postponed; and secondly, that these needs have accumulated in the last few years and so, the political pressure accumulated should account for reorientation in public expenditure, increasingly favouring the social sector, specially housing. Some Í€œcrucial topicsÍ€ derived from this rather optimistic view are furtherly explored.